Saberes e cuidados: um estudo de atores socioambientais na Bacia do Prata - Vieira, Marco Antônio Bilo (2014)
This study aims to investigate the action of four environmental actors, located in the La Plata Basin, which, throughout their stories, promote sustainability through knowledge and cares as transformative forces of the reality. This investigation aims at presenting and understanding these forces, as well as the description of the organizational activities, related to the guiding themes of emancipation and empowerment, along with labor collectives. It also enables knowledge of similarities and differences in the actions of these actors regarding the impressions of the daily challenges which they experience. The methodology is investigative, outlined by the study of multiple cases and, remarkably, it has an interdisciplinary nature and social character. Thus, its main methodological tools are questionnaires for collecting organizational data and the application of the SWOT matrix. Thus, the results presented the descriptions of the organization name, the original region, applied themes, areas of activity, professional staff, assisted public, the timeline, the initial social needs, theoretical influences and the setting of sustainable rural development. Also, organizational perceptions were analyzed relating to the dimensions of sustainability in specific thematic indicators. Consequently, the study reveals that these environmental actors consider the existence of favorable challenges to their performance and organizational skills, since the knowledge and care that grow with the assisted public are regarded as principles and practices of environmental transformation.